Research of the chemical composition of Artemisia tschernieviana Bess. by gas chromatography method with mass detection - O. I. Panasenko; V. I. Mozul; O. M. Denysenko; I. I. Aksonova; V. V. Holovkin (Zaporozhye State Medical University, 2021)
The aim of the work was to study chromato-mass spectroscopic of Artemisia tschernieviana Bess. grass and to establish possible prospects for the use of this plant in medical practice. Materials and methods. Artemisia tschernieviana Bess. grass was chosen as the object of research. Raw materials were collected in July 2021 in the flowering phase (Zaporizhzhia). The tincture was obtained by maceration and the raw material was extracted with methyl alcohol at room temperature for 10 days according to the method of making tinctures. The study of the chemical composition of Artemisia tschernieviana Bess. Grass was carried out using gas chromatograph Agilent 7890B GC System (Agilent, Santa Clara, CA, USA) with mass spectrometric detector Agilent 5977 BGC/MSD (Agilent, Santa Clara, CA, USA) and chromatographic column DB-5ms (30 m × 250 μm × 0.25 μm). Results. During the study it was found that the composition of Artemisia tschernieviana Bess. grass includes 21 compounds (2 in the isomeric state). β-myrcene (17.22 %), sabinene (14.54 %), 2-(4a,8-dimethyl-7-oxo-1,2,3,4,4a,7-hexahydronaphthalen-2-yl) propionic acid (11.57 %), 2-dodecen-1-yl-succinic anhydride (10.84 %) and chamazulene (9.02 %) accounted for the largest percentage. According to the literature review, myrcene has antibacterial, anesthetic and analgesic effects. Sabinene is characterized by antibacterial action. 2-(4a,8-dimethyl-7-oxo-1,2,3,4,4a,7-hexahydronaphthalen-2-yl)-propionic acid is a fatty acid with possible antibacterial and anti-inflammatory activity. 2-dodecen-1-yl-succinic anhydride is used to produce anhydride-modified form of insulin that can be used in the treatment of diabetes. Hamazulen has anti-inflammatory activity. Conclusions. In view of all the above, we can conclude that Artemisia tschernieviana Bess. grass can be recommended for further research as a source of potential anti-inflammatory and antibacterial agents.